Fault tolerance conceptual strategy for a quadcopter drone with rotor failure - Zaludin, Zairil A. (The Research Publication, 2023)
The ability of a quadcopter drone to maintain its attitude relies solely on its four rotors. If even one motor fails, the drone loses its ability to hold attitude and altitude. This paper explores a new fault tolerance solution to enhance attitude control for quadcopter drones following the complete loss of a single rotor. By following the fundamental principle of balancing forces and moments on a quadrotor drone, the paper demonstrates that it is feasible to land the drone safely by minimizing roll, pitch, and yaw when a rotor fails. The concept centers around thrust vectoring, which allows an opposite motor to tilt independently. The results indicate that tilting the opposite rotor by 45o provides better management of the drone’s roll, pitch, and yaw, enabling the incapacitated drone to land in a more controlled and manageable manner. The paper includes simulation results and a summary table of the novel idea’s performance enhancements.